TI_GERICHTE 17.2011.1 vom 8. April 2011 , Omicidio colposo. Violazione dell'art. 32 cpv. 1 LCStr. Definizione di nesso di causalità naturale ed adeguata - TI Tribunale d'appello (2011)
Omicidio colposo. Violazione dell'art. 32 cpv. 1 LCStr. Definizione di nesso di causalità naturale ed adeguata